2022
DOI: 10.1038/s41598-022-09940-0
|View full text |Cite
|
Sign up to set email alerts
|

Applications of zeolite-zirconia-copper nanocomposites as a new asphaltene inhibitor for improving permeability reduction during CO2 flooding

Abstract: Using nanoparticles for adsorbing asphaltene was known as an efficient method among researchers for crude oil upgrading. In this study, zeolite-zirconia-copper nanocomposites (NCs) have been synthesized and characterized with Scanning electron microscopy (SEM), X-ray diffraction (XRD), Brunauer–Emmett–Teller (BET), and energy-dispersive X-ray (EDX). Then, CO2-oil interfacial tension (IFT) tests, Ultraviolet–visible spectroscopy (UV–Vis) Langmuir and Freundlich isotherm models, asphaltene precipitation tests at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…In the presence of zeolite, asphaltene precipitation decreased from 14.24 to 6.25 wt.% and 8.40 wt.%, respectively. Furthermore, in CO 2 dynamic tests, it was observed that zeolite‑zirconia‑copper nanocomposites had high potential for improving permeability impairment, reducing porosity, and decreasing the asphaltene deposition rate 16 . Li et al investigated the effectiveness of three nanoparticle types—NiO, SiO 2 , and Fe 3 O 4 —in inhibiting asphaltene precipitation in water-wet porous media, attributing their efficacy to their high surface area-to-volume ratio, strong adsorption capacity, and excellent suspension characteristics 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of zeolite, asphaltene precipitation decreased from 14.24 to 6.25 wt.% and 8.40 wt.%, respectively. Furthermore, in CO 2 dynamic tests, it was observed that zeolite‑zirconia‑copper nanocomposites had high potential for improving permeability impairment, reducing porosity, and decreasing the asphaltene deposition rate 16 . Li et al investigated the effectiveness of three nanoparticle types—NiO, SiO 2 , and Fe 3 O 4 —in inhibiting asphaltene precipitation in water-wet porous media, attributing their efficacy to their high surface area-to-volume ratio, strong adsorption capacity, and excellent suspension characteristics 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Resins, fatty acids such as naphthenic acids, porphyrins, wax crystals, and other crude oil components are also surface active, although they cannot generate stable emulsions on their own most of the time [15][16][17][18]. Asphaltenes in oil are solubilized by resins, which remove them from the interface, decreasing emulsion stability [19,20]. Oil production is hindered by surface-active components, causing flow assurance issues.…”
Section: Introductionmentioning
confidence: 99%